Synergistic Engineering of Sulfur Vacancies and Heterointerfaces in Copper Sulfide Anodes for Aqueous Zn‐Ion Batteries with Fast Diffusion Kinetics and an Ultralong Lifespan. Issue 21 (16th April 2022) - Lei, Qi; Zhang, Jiaqian; Liang, Zhaofeng; Yue, Yang; Ren, Zhiguo; Sun, Yuanhe; Yao, Zeying; Li, Ji; Zhao, Yuanxin; Yin, Yaru; Huai, Ping; Lv, Zhengxing; et al.
Abstract: Aqueous Zn‐ion batteries (AZIBs) are promising candidates for implementing large‐scale energy storage, but the adverse side reactions and unsatisfactory cycle life brought by Zn‐metal anodes limit their potential in applications. Herein, an ingenious synthesized CuS1–x @polyaniline (PANI) is proposed as an attractive conversion‐type Zn‐metal‐free anode for AZIBs, in which appropriate S‐vacancies and PANI heterointerfaces can be simultaneously constructed. This "killing three birds with one stone" strategy stabilizes the anode structure by utilizing organic–inorganic heterointerfaces and enhances Zn 2+ storage, benefiting from abundant S‐vacancies, as well as initiating fast Zn 2+ transport kinetics based on the joint effect of the two. Operando X‐ray absorption fine structure and synchrotron X‐ray diffraction further reveal the highly reversible conversion reaction of CuS1–x @PANI via a distinct crystallization–amorphous transformation mechanism. These features endow CuS1–x @PANI with sufficient zinc‐ion storage capacity (215 mA h g −1 at 100 mA g −1 ) and reliable current abuse tolerance (154.3 mA h g −1 at 1 A g −1 after 1000 cycles). Moreover, when matched with the optimized Znx MnO2 cathode, the full battery achieves a record‐high cycling performance of 10 000 cycles (80% capacity retention) at a superhigh current density of 10 A g −1 . This study provides new opportunities for developing high‐performance rocking‐chair AZIBs. Abstract : A CuS microflower with S‐vacancies and polyaniline (PANI) heterointerfaces concurrently engineered is introduced as an attractive anode for aqueous Zn‐ion batteries. The S‐vacancies and PANI heterointerfaces synergistically improve the Zn 2+ adsorption capacity, structural stability, and ion transport dynamics, thus enabling the CuS with high specific capacity and rate performance. Moreover, CuS1–x @PANI||Znx MnO2 full cells can operate with 80% capacity retention after 10 000 cycles.